RETRO-POPE: A Retrospective, Multicenter, Real-World Study of All-Cause Mortality in COPD - Koblizek, Vladimir; Milenkovic, Branislava; Svoboda, Michal; Kocianova, Jana; Holub, Stanislav; Zindr, Vladimir; Ilic, Miroslav; Jankovic, Jelena; Cupurdija, Vojislav; Jarkovsky, Jiri; Popov, Boris; Valipour, Arschang (International journal of chronic obstructive pulmonary disease, 2023)
PURPOSE: The Phenotypes of COPD in Central and Eastern Europe (POPE) study assessed the prevalence and clinical characteristics of four clinical COPD phenotypes, but not mortality. This retrospective analysis of the POPE study (RETRO-POPE) investigated the relationship between all-cause mortality and patient characteristics using two grouping methods: clinical phenotyping (as in POPE) and Burgel clustering, to better identify high-risk patients. PATIENTS AND METHODS: The two largest POPE study patient cohorts (Czech Republic and Serbia) were categorized into one of four clinical phenotypes (acute exacerbators [with/without chronic bronchitis], non-exacerbators, asthma-COPD overlap), and one of five Burgel clusters based on comorbidities, lung function, age, body mass index (BMI) and dyspnea (very severe comorbid, very severe respiratory, moderate-to-severe respiratory, moderate-to-severe comorbid/obese, and mild respiratory). Patients were followed-up for approximately 7 years for survival status. RESULTS: Overall, 801 of 1,003 screened patients had sufficient data for analysis. Of these, 440 patients (54.9%) were alive and 361 (45.1%) had died at the end of follow-up. Analysis of survival by clinical phenotype showed no significant differences between the phenotypes (P=0.211). However, Burgel clustering demonstrated significant differences in survival between clusters (P<0.001), with patients in the "very severe comorbid" and "very severe respiratory" clusters most likely to die. Overall survival was not significantly different between Serbia and the Czech Republic after adjustment for age, BMI, comorbidities and forced expiratory volume in 1 second (hazard ratio [HR] 0.80, 95% confidence interval [CI] 0.65-0.99; P=0.036 [unadjusted]; HR 0.88, 95% CI 0.7-1.1; P=0.257 [adjusted]). The most common causes of death were respiratory-related (36.8%), followed by cardiovascular (25.2%) then neoplasm (15.2%). CONCLUSION: Patient clusters based on comorbidities, lung function, age, BMI and dyspnea were more likely to show differences in COPD mortality risk than phenotypes defined by exacerbation history and presence/absence of chronic bronchitis and/or asthmatic features.
Keywords: respiratory; Phenotype; dyspnoe; chronická bronchitida; lidé; Dyspnea; Pulmonary Disease, Chronic Obstructive; survival; COPD; retrospektivní studie; Central and Eastern Europe; chronická obstrukční plicní nemoc; clinical phenotype; progrese nemoci; Disease Progression; Bronchitis, Chronic; Forced Expiratory Volume; cluster; mortality; fenotyp; Retrospective Studies; usilovný výdechový objem; Humans